2015
DOI: 10.1177/0954405415578579
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the ultrasonic vibration effect in incremental sheet metal forming process

Abstract: The mechanism of incremental sheet metal forming is based on plastic and localized deformation of sheet metal. The sheet metal is formed using a hemispherical-head tool in accordance with the path programmed into the computer numerical control milling machine controller. Experimental and numerical analyses have been performed previously on the application of ultrasonic vibration to various metal forming processes. However, thus far, the effects of ultrasonic vibration on incremental sheet metal forming have no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 34 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…First of all, Vahdati et al [83] used an ultrasonic vibration during the ISF process and conducted experimental tests. They found that the increase in ultrasonic vibration of forming punch resulted in the decrease in forming force, spring-back rate and surface roughness.…”
Section: Influence Of Other Parametersmentioning
confidence: 99%
“…First of all, Vahdati et al [83] used an ultrasonic vibration during the ISF process and conducted experimental tests. They found that the increase in ultrasonic vibration of forming punch resulted in the decrease in forming force, spring-back rate and surface roughness.…”
Section: Influence Of Other Parametersmentioning
confidence: 99%
“…It improved the surface quality and reduced the distortion of parts. Iranian scholar M. Vahdati et al [13], using experiments, proved the effects of ultrasonic vibration (UV) on SPIF in reducing the axial force, springback, and surface roughness. Iranian scholar S. Amini et al [14] applied axial high frequency and low amplitude UV to the forming tool to form a 1050 aluminum straight groove.…”
Section: Introductionmentioning
confidence: 99%
“…This used the principle that at cryogenic temperatures, there is enhanced tensile elongation for certain face centred cubic alloys, resulting in increased strain hardening. Vahdati et al [119] have developed an ultrasonic vibration assisted setup. Tests were carried out on AA 1050-O sheets and their results showed improvement in forces, accuracy and surface finish of the formed parts.…”
Section: Optimized Workpiece Orientationmentioning
confidence: 99%